The Crimes of Insult and Defamation in Cyberspace under Qatari and Emirati Legislation : A Comparative Analytical Study - Al-Muslimmani, Aisha; Al-Sahlawi, Noura (Journal of Legal Sciences, 2026)
This research addresses the crimes of defamation and libel in cyberspace through an analytical study and comparison between Qatari and Emirati legislation. It explains the nature and scope of the crimes of defamation and libel, stating that they do not differ significantly from traditional crimes. They are considered complaints crimes, in which filing a criminal case depends on filing a complaint. It also examines the procedural and substantive provisions of the crimes, the elements of the crime, the penalties prescribed for them, and their adequacy. It also highlights the need to increase the penalties for the crimes of defamation and libel in cyberspace, given their widespread prevalence, particularly on social media, and the laxity of individuals in this regard. It is also necessary to amend the provisions of the UAE Penal Code, specifically the section on complaints. The UAE legislature has stipulated a partially lengthy statute of limitations of three months. Therefore, we recommend that the legislature reduce this period and follow the Qatari legislature’s approach, setting the statute of limitations for complaints at 30 days. Through this, we have reached several conclusions and recommendations.